2022
DOI: 10.3390/separations9090256
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biosorption of Methylene Blue Dye onto Agricultural Products: A Critical Review

Abstract: Due to their higher specific area and, in most cases, higher adsorption capacity, nanomaterials are noteworthy and attractive adsorbents. Agricultural products that are locally available are the best option for removing methylene blue (MB) dye from aqueous solutions. Because it is self-anionic, FT-IR and SEM investigations of biosorption have confirmed the role of the functional group and its contribution to the formation of pores that bind cationic dye. It is endothermic if the adsorption of MB by an adsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
0
11
0
7
Order By: Relevance
“…The displacement of these peaks in the spectrum of the treatment plant may have been due to the formation of interactions between the Ceratophyllum plant and the molecules of the AB92 dye. Studies have shown that the functional groups of amines, hydroxyl, carbonyl, and carboxyl in plants can play an important role in the interaction between plants and dye molecules (Liu & Wang, 2023;Sah et al, 2022). This could indicate the occurrence of the first phase of detoxification, i.e.…”
Section: Spectral Analysis Of Irmentioning
confidence: 99%
“…The displacement of these peaks in the spectrum of the treatment plant may have been due to the formation of interactions between the Ceratophyllum plant and the molecules of the AB92 dye. Studies have shown that the functional groups of amines, hydroxyl, carbonyl, and carboxyl in plants can play an important role in the interaction between plants and dye molecules (Liu & Wang, 2023;Sah et al, 2022). This could indicate the occurrence of the first phase of detoxification, i.e.…”
Section: Spectral Analysis Of Irmentioning
confidence: 99%
“…[45] Due to these properties, there are biosorption studies on the removal of many pollutants such as dyes and heavy metals from agricultural wastes. [46,47] In addition, various organic and inorganic pollutants are removed by obtaining NPs from agricultural wastes by various methods. [48][49][50] Because the use of agricultural wastes in nanotechnology is increasing day by day due to their low toxic properties, [51] therefore, it is essential to recycle these wastes within the framework of "sustainable development" and "green economy.…”
Section: Introductionmentioning
confidence: 99%
“…All of these elements are active ion exchange molecules [4] and known binding sites for dyes whereas the presence of À C=O and À OH functional groups was confirmed through FT-IR analysis, and surface examinations using SEM verified their involvement in binding positive cationic dyes like MB, which can be utilized in both conventional and nanoproduct configurations. [18] The physical activation of the raw materials can cause a loss of these functional groups during thermal activation, which could be the possible reason for the reduction in adsorption capacity. [5] In the global, there are more than 5000 distinct date palm cultivars, exhibiting variations in nutritional, morphological and genetic characteristics, however, the number of commercial cultivars remains restricted.…”
Section: Introductionmentioning
confidence: 99%